In vitro effects of fluticasone propionate on IL-13 production by mitogen-stimulated lymphocytes - Gabriele Di Lorenzo; Maria Luisa Pacor; Maria Esposito Pellitteri; Sebastiano Gangemi; Patrizia Di Blasi; Giuseppina Candore; Alfredo Colombo; Domenico Lio; Calogero Caruso (Mediators of Inflammation)
Background: Corticosteroid administration produces multiple immunomodulatory effects, including down-regulation of cytokine production by CD4 T lymphocytes. Fluticasone propionate (FP) (Glaxo Smith&Kline, Greenford, UK), a highly lipophilic topical corticosteroid, has been shown to be safe and effective in the treatment of asthma and of both seasonal and perennial rhinitis.